A Case Study of Cattle Prices in Nicaragua - Augustin, Jameson; Lopez, Jose; Leiva, Ervin; Bakhtavoryan, Rafael (Journal of Applied Business and Economics, 2021)
Latin America has become the leading region for beef and poultry exports worldwide (FAO, 2020a). We conduct a case study of cattle prices in Nicaragua, the leading meat producing country in Central America.1 Using data on futures on feeder cattle prices from the Chicago Mercantile Exchange Group (CME) supplemented with a two-year data on 2,520 sales transactions from 99 auctions from the Nicaraguan Cattle Auction (NCA), this study conducts a hedonic price analysis for cattle auctioned in Nicaragua. In particular, the study empirically identifies factors affecting price differentials for cattle and examines their correlation with the futures market. Our results show that weight, lot size, and class are among statistically significant factors impacting cattle auction prices while their correlation with the futures market is significant for six out of the eight futures variables corresponding to the contract months at the CME. The results of the study help Nicaraguan cattle buyers and sellers understand information from the futures market to predict price differences and reduce price risk and uncertainty.